Numerical Simulation of Interaction Between Red Blood Cell with Surrounding Fluid in Poiseuille Flow (Advances in Applied Mathematics and Mechanics, 2018)
In this research, motion and deformation of a red blood cell (RBC) in a microchannelwith stenosis is investigated by combined Lattice Boltzmann-ImmersedBoundary method. The fluid flow occurs due to the pressure difference between the inletand the outlet of the microchannel. The immersed boundary algorithm guaranteesthat there is no relative velocity between the RBC and fluid. Therefore, mass transferalong the immersed border does not occur. It can be seen that the healthy RBC hasmore deformation and passes the stenosis more easily while the sick one passes the stenosiswith less deformation and returns to its initial state faster. Increasing the pressure gradient(i.e., increasing Reynolds number) would cause more deformation of the RBC.It is found that a healthy RBC moves faster than a sick one along the microchannel.Blood pressure increases due to the presence of stenosis and low deformable RBCs. Itis the reason of many serious diseases including cardiovascular diseases. The resultsof this paper were compared to the previous valid results and good agreements wereobserved.